Spectrum of Activity and Mechanisms of Resistance of Various Nucleoside Derivatives against Gammaherpesviruses - Coen, Natacha (Antimicrob Agents Chemother, 2014)
The susceptibilities of gammaherpesviruses, including Epstein-Barr virus (EBV), Kaposi's sarcoma-associated herpesvirus (KSHV), and animal rhadinoviruses, to various nucleoside analogs was investigated in this work. Besides examining the antiviral activities and modes of action of antivirals currently marketed for the treatment of alpha- and/or betaherpesvirus infections (including acyclovir, ganciclovir, penciclovir, foscarnet, and brivudin), we also investigated the structure-activity relationship of various 5-substituted uridine and cytidine molecules. The antiviral efficacy of nucleoside derivatives bearing substitutions at the 5 position was decreased if the bromovinyl was replaced by chlorovinyl. 1-β-d-Arabinofuranosyl-(E)-5-(2-bromovinyl)uracil (BVaraU), a nucleoside with an arabinose configuration of the sugar ring, exhibited no inhibitory effect against rhadinoviruses but was active against EBV. On the other hand, the fluoroarabinose cytidine analog 2′-fluoro-5-iodo-aracytosine (FIAC) showed high selectivity indices against gammaherpesviruses that were comparable to those of brivudin. Additionally, we selected brivudin- and acyclovir-resistant rhadinoviruses in vitro and characterized them by phenotypic and genotypic (i.e., sequencing of the viral thymidine kinase, protein kinase, and DNA polymerase) analysis. Here, we reveal key amino acids in these enzymes that play an important role in substrate recognition. Our data on drug susceptibility profiles of the different animal gammaherpesvirus mutants highlighted cross-resistance patterns and indicated that pyrimidine nucleoside derivatives are phosphorylated by the viral thymidine kinase and purine nucleosides are preferentially activated by the gammaherpesvirus protein kinase.